2022
DOI: 10.2147/dmso.s383880
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Obesity and Overweight with Cervical Vascular Function Among Healthy Populations

Abstract: Purpose To study the effects of obesity and overweight on carotid vascular function among healthy populations by carotid ultrasound (CAU) and transcranial Doppler (TCD). Materials and Methods Basic clinical characteristics, CAU and TCD parameters were collected from recruited healthy individuals. Firstly, all participants were divided into three groups: normal, overweight and obese. Then, the variability of basic clinical characteristics and lipids between the three gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Obesity is now widely recognised as a risk factor for various chronic ailments and is closely linked with an elevated occurrence of diabetes, hypertension, and cardiovascular and cerebrovascular diseases. 11 , 12 Available data suggest that in 2018, the proportion of individuals suffering from obesity in China had risen by more than two-fold to 8.1% from 3.1% in 2004. 13 A recent study found that 15.8 million Chinese adults have a current prevalence of obesity of 14.1% and overweight of 34.8%.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is now widely recognised as a risk factor for various chronic ailments and is closely linked with an elevated occurrence of diabetes, hypertension, and cardiovascular and cerebrovascular diseases. 11 , 12 Available data suggest that in 2018, the proportion of individuals suffering from obesity in China had risen by more than two-fold to 8.1% from 3.1% in 2004. 13 A recent study found that 15.8 million Chinese adults have a current prevalence of obesity of 14.1% and overweight of 34.8%.…”
Section: Discussionmentioning
confidence: 99%